ON LYTOCESTUS KOPARDAENSIS N.SP. CESTODA LYTOCESTIDAE HUNTER, FROM A FISH IN MAHARASHTRA STATE, INDIA. - SHINDE, G.B.; BORDE, SUNITA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1999)
The paper contains, description of a new species of genus Lytocestus (Cohn, 1908) Hunter, 1927 L. kopardaensis n.sp. differs from all the earlier reported species, in having head long, elongated, narrow anteriorly, neck is medium in length with irregular margins, testes numerous 1600-1700 (1650), cirrus pouch large, preovarian, obliquely placed, ovary distinctly bilobed with irregular margins; uterus a coiled tube, loop shaped; vitellaria are follicular, corticular in position. in 2-3 rows on each side, from the middle region to the level of cirrus pouch.